2022
DOI: 10.1101/2022.03.10.22272227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stable Sparse Classifiers predict cognitive impairment from gait patterns

Abstract: Background: Although gait patterns disturbances are known to be related to cognitive decline, there is no consensus on the possibility of predicting one from the other. It is necessary to find the optimal gait features, experimental protocols, and computational algorithms to achieve this purpose. Purposes: To assess the efficacy of the Stable Sparse Classifiers procedure (SSC) for discriminating young and older adults, as well as healthy and cognitively impaired elderly groups from their gait patterns. To iden… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…A summarized cognitive index (MDCog), based on the Mahalanobis distance from normative data, was calculated. In another study (Aznielle-Rodríguez et al, 2022 ), we have demonstrated that MDCog has a closer relationship with STGF than other cognitive measures. An additional goal was to use SSC to identify the best combination of walking tasks and associated STGF to predict cognitive status.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…A summarized cognitive index (MDCog), based on the Mahalanobis distance from normative data, was calculated. In another study (Aznielle-Rodríguez et al, 2022 ), we have demonstrated that MDCog has a closer relationship with STGF than other cognitive measures. An additional goal was to use SSC to identify the best combination of walking tasks and associated STGF to predict cognitive status.…”
Section: Introductionsupporting
confidence: 52%
“…This disbalance in the sample could affect any classifier used, not only SSC. Further work should examine the possibility of predicting cognitive scores (not only classifying into groups) through regression analysis, a goal for which preliminary results are presented in Aznielle-Rodríguez et al ( 2022 ). Also, SSC should be compared with other classifiers, not only SVM and LDA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation